2013
DOI: 10.1089/apc.2013.0208
|View full text |Cite
|
Sign up to set email alerts
|

The Reproductive Health Behaviors of HIV-Infected Young Women in the United States: A Literature Review

Abstract: HIV-infected young women in the United States have important reproductive health needs that are made more complex by their HIV status. We searched Pubmed and relevant bibliographies to identify 32 articles published from 2001 to July 2012 that described the prevalence, correlates, and characteristics of the sexual activity, relationships, pregnancy intentions, HIV status disclosure, and contraceptive and condom use among US HIV-infected adolescents and young women. Our synthesis of those articles found that, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Although there has been increased access to ART, studies examining sexuality and reproduction for women living with HIV still show that HIV impacts sexuality and reproduction negatively (Carter et al, 2017a; Greene, Ion, Kwaramba, Smith, & Loutfy, 2015; Rahangdale et al, 2014). Women with HIV therefore face unique challenges, such as in partner relationships, sexual satisfaction and childbearing (Bharat & Mahendra, 2007; Carter et al, 2013; Florence et al, 2004). Many women living with HIV have a desire to give birth to a child (Carter et al, 2017b; Wessman et al, 2015), a desire which can further increase feelings of stigmatization, shame and fear (Sandelowski & Barroso, 2003; Sanders, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been increased access to ART, studies examining sexuality and reproduction for women living with HIV still show that HIV impacts sexuality and reproduction negatively (Carter et al, 2017a; Greene, Ion, Kwaramba, Smith, & Loutfy, 2015; Rahangdale et al, 2014). Women with HIV therefore face unique challenges, such as in partner relationships, sexual satisfaction and childbearing (Bharat & Mahendra, 2007; Carter et al, 2013; Florence et al, 2004). Many women living with HIV have a desire to give birth to a child (Carter et al, 2017b; Wessman et al, 2015), a desire which can further increase feelings of stigmatization, shame and fear (Sandelowski & Barroso, 2003; Sanders, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2 Additionally, in a sample of adolescent females living with HIV, 70-80% report a desire to have a child now or some time in the future. 6 Pregnancy desires and childbearing motivations among young women living with HIV are comparable to women who are not HIV positive. 7 Finger et al 8 found that history of victimization as a child, having fewer living children, decreased disclosure of HIV status, increased likelihood of sexual intercourse and oral sex, and decreased condom use are correlated with desire for pregnancy in sample of young women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…3 The need and desire for FP services is substantial among HIV-positive persons in both resource-limited [4][5][6][7][8][9][10] and resource-rich [11][12][13][14] settings. The unmet need for FP services is particularly high in Kenya; one study found that nearly 70% of HIV-positive women in western Kenya indicate wishing to delay their fertility for another 2 years or not have any further children.…”
mentioning
confidence: 99%